Nationalist passions - Kaufman, Stuart J. (Cornell University Press, 2015)
"Nationalist and ethnic conflict can take many forms, from genocidal violence and civil war to protest movements and peaceful squabbles in democracies. Nationalist Passions poses a stark challenge to extreme rationalist understandings of political conflict. Stuart J. Kaufman elaborates a compelling theory of ethnic politics to explain why ethnic violence erupts in some contexts and how peace is maintained in others. At the core of Kaufman's theory is an assertion that conflicts are initiated due to popular "symbolic predispositions"--Biases of all kinds--and perceptions of threat. Kaufman puts his theory to the test in a range of conflicts. He examines some highly violent episodes, among them the Muslim rebellion in the southern Philippines beginning in the 1970s; the civil war in southern Sudan that began in the 1980s; and the Rwanda genocide of 1994. Kaufman also analyzes other situations in which leaders attempted to tame the violence that nationalist passions can generate. In India, Mahatma Gandhi mobilized an overtly nonviolent movement but failed in his efforts to prevent the rise of Muslim-Hindu communal violence. In South Africa, Nelson Mandela and F.W. de Klerk ended apartheid, but not without terrible cost--more than fifteen thousand people died while the negotiations were under way. In Tanzania, however, Julius Nyerere led one of the few ethnically diverse countries in the world with almost no ethnic violence. Nationalist Passions is essential reading for policymakers, international aid workers, and all others who seek to find the best possible outcomes for future internal and interstate clashes."--Publisher information.